School-based diet and physical activity interventions and weight-related outcomes among children and adolescents in Africa: a systematic review and meta-analysis - Barbara Adimchinobi Onyeonu; Favour Chiamaka Kalu; Kosisochukwu Chidinma Igbokwe; Uzoamaka Victoria Thomspon; Favour Chidinma Okezie; Anuoluwapo Funmilayo Taiwo; Gideon Onyedikachi Iheme (BMC Public Health, 2026)
Abstract Introduction The increasing prevalence of Obesity and associated health risks in LMICs underscores the urgent need to adopt an integrated approach to Obesity prevention and management. This systematic review aims to assess the impact of school-based diet and physical activity interventions on weight-related outcomes among children and adolescents in Africa. Methods This systematic review was registered with PROSPERO (CRD42023450307) and reported according to the PRISMA statement. A comprehensive literature search was conducted across three databases, PubMed, Google Scholar and African Journals Online from January 2000 to December 2025. Result Our search identified a total of 11 eligible studies, with modest to low risk of bias, of which majority of the studies were published within the last decade (63.6%), and conducted in South Africa (72.7%). These studies were predominantly quasi-experimental (70%) or cluster randomized control trail (18.2%) in design. The majority (73%) interventions were delivered in primary school settings and participants were mainly engaged in group activities. The bulk of the interventions were multi-component, comprising physical activity, alongside nutrition, and other health/behavioural interventions. Overall, the studies reported modest improvements in elevated adiposity and maintenance of normal weight status in the intervention groups. However, this translated into a non-significant effect in the meta-analysis of nine intervention comparisons on BMI-for-age (MD = 0.03, 95% CI: −0.24 to 0.29; p = 0.813; I² = 69.0%), although combined nutrition and physical activity interventions showed reductions in a few comparisons. Conclusion School-based diet and physical activity interventions show potential to improve adiposity and maintain healthy weight status among African children and adolescents, particularly when combined. However, the overall effect on BMI-for-age was not significant, highlighting the need for more geographically diverse and methodologically robust evidence across Africa.